Analisis Isi Desain Pengembangan Kurikulum Merdeka pada Mata Pelajaran Pendidikan Agama Islam di SDN 066 Bengkulu Utara - Ai Siti Hodijah; Desy Eka Citra Dewi; Ayu Netasya Putri (Al-Khair Journal: Management Education, 2024)
Abstract: The development of an independent curriculum is still difficult to apply to PAI subjects, because the content of the design still overlaps with other subjects. The purpose of the research is to analyze the content of the design of the development of the independent curriculum in the subject of Islamic Religious Education at SDN 066 North Bengkulu. Using a descriptive qualitative method. The results of the study show that the content of the independent curriculum design of Islamic Religious Education subjects includes (1) Al-Qur'an and Hadith which contain learning hijaiya, harakat, makhrojul letters, writing, reading and memorizing short letters, (2) Aqidah which contains: pillars of faith and pillars of Islam, (3) Morals which contains: understanding of commendable behaviors, (4) Fiqh which contains: Halan and Haram, Thaharah, Fasting, Sunnah Prayer, Fardhu Prayer. Hajj and Qurban, zakat, and infaq, and (5) SKI which contains: The Story of the Prophets and Messengers, The Hijrah Journey of the Prophet Muhammad, and Khulafaurrasyidin. Therefore, it can be concluded that the content of the design of the development of the independent curriculum in the subject of Islamic Religious Education includes the design of the implementation of the independent curriculum, the elements and achievements of the Islamic Religious Education subject, the pouring of achievements per element into the goals and learning flow made to become a teaching module. So it can be suggested, for the development of an independent curriculum, then increase the analysis of content and curriculum design in schools.Keywords: Analysis, Content of Independent Curriculum Development Design, Islamic Religious Education. Abstrak: Pengembangan kurikulum merdeka masih sulit diterapkan pada mata pelajaran PAI, karena isi desain masih tumpang tindih dengan mata pelajaran lain. Tujuan penelitian untuk menganalisis isi desain pengembangan kurikulum merdeka pada mata pelajaran Pendidikan Agama Islam di SDN 066 Bengkulu Utara. Menggunakan metode kualitatif deskriptif. Hasil penelitian menunjukkan bahwa isi desain kurikulum merdeka mata pelajaran Pendidikan Agama Islam meliputi (1) Al-Qur’an dan Hadis yang berisi pembelajaran hijaiya, harakat, makhrojul huruf, penulisan, pembacaan dan penghafalan surat-surat pendek, (2) Aqidah yang berisi: rukun iman dan rukun islam, (3) Akhlak yang berisi: pemahaman terhadap perilaku-perilaku terpuji, (4) Fiqh yang berisi: Halan dan Haram, Thaharah, Puasa, Sholat sunah, Shalat Fardhu. Haji dan Qurban, zakat, dan infak, dan (5) SKI yang berisi: Kisah para nabi dan Rasul, Perjalanan Hijrah nabi Muhammad, dan Khulafaurrasyidin. Oleh karena itu, dapat disimpulkan bahwa isi desain pengembangan kurikulum merdeka pada mata pelajaran Pendidikan Agama Islam meliputi rancangan penerapan kurikulum merdeka, elemen dan capaian mata pelajaran Pendidikan Agama Islam, penuangan capaian per elemen kedalam tujuan dan alur pembelajaran dibuat untuk menjadi modul ajar. Sehingga dapat disarankan, untuk pengembangan kurikulum merdeka, maka tingkatkan analisis isi dan desain kurikulum di sekolah.Kata kunci: Analisis, Isi Desain Pengembangan Kurikulum Merdeka, Pendidikan Agama Islam.